Pandemic Uncertainty and Socially Responsible Investments - Zhu, Wenzhong; Yang, Jiajia; Lv, Han; Zhuang, Meier (Frontiers in Public Health, 2021)
This paper examines the effects of pandemic uncertainty on socially responsible investments. We use the overall corporate sustainability performance index in the Global-100 Most Sustainable Corporations in the World dataset to measure socially responsible investments. The pandemics uncertainty across the countries are also measured by the World Pandemic Uncertainty Index. We focus on the panel dataset from 2012 to 2020, and the results show that the World Pandemic Uncertainty Index is positively related to socially responsible investments. The main findings remain significant when we utilize various panel estimation techniques.